Salt Sensitivity of Angiogenesis Inhibition–Induced Blood Pressure Rise: Role of Interstitial Sodium Accumulation?. Issue 5 (May 2017) - Lankhorst, Stephanie; Severs, David; Markó, Lajos; Rakova, Natalia; Titze, Jens; Müller, Dominik N.; Danser, A.H. Jan; van den Meiracker, Anton H.
Abstract : In response to salt loading, Na + and Cl − accumulate in the skin in excess of water, stimulating skin lymphangiogenesis via activation of the mononuclear phagocyte system cell-derived vascular endothelial growth factor-C–vascular endothelial growth factor type 3 receptor signaling pathway. Inhibition of this pathway results in salt-sensitive hypertension. Sunitinib is an antiangiogenic, anticancer agent that blocks all 3 vascular endothelial growth factor receptors and increases blood pressure. We explored the salt dependency of sunitinib-induced hypertension and whether impairment of skin lymphangiogenesis is an underlying mechanism. Normotensive Wistar–Kyoto rats were exposed to a normal or high salt with or without sunitinib administration. Sunitinib induced a 15 mm Hg rise in telemetrically measured blood pressure, which was aggravated by a high-salt diet (HSD), resulting in a decline of the slope of the pressure–natriuresis curve. Without affecting body weight, plasma Na + concentration or renal function, Na + and Cl − skin content increased by 31% and 32% with the high salt and by 49% and 50% with the HSD plus sunitinib, whereas skin water increased by 17% and 24%, respectively. Skin mononuclear phagocyte system cell density increased both during sunitinib and a HSD, but no further increment was seen when HSD and sunitinib were combined. HSD increased skin lymphangiogenesis, while sunitinib tended to decrease lymphangiogenesis, both during a normal-salt diet and HSD. We conclude that sunitinib induces hypertension that is aggravated by high salt intake and not accompanied by impaired skin lymphangiogenesis. Abstract : Supplemental Digital Content is available in the text.